NAZI INTERNE PROPAGANDA IN DIE TWEEDE WÊRELDOORLOG - Kotze, J.S. (Scientia Militaria - South African Journal of Military Studies, 2012)
Adolf Hitler considered propaganda as a tactical weapon which should be used in warfare. The Second World War proved that it was no super weapon, and that It could not be used in isolation, but it Is generally agreed that Nazi internal propaganda played a prominent part in upholding solidarity of morale in Germany during the last two years of the war. An indispensable condition for this achievement was the totalitarian political system in Germany which made monopolistic state control of propaganda activities possible, and secured effective canalisation and co-ordination of all such activities. In addition suitable propaganda themes were developed, and were continually adjusted to changing circumstances, and a constant issue of propaganda was meticulously maintained. Goebbels considered public opinion to be open to manipulation, even if through fabricated propaganda tricks, and managed to achieve this. In the last weeks of the war, however, he had to reap the bitter fruits of thoughtless propaganda, unfulfilled promises and blatant Iies. Even he could not escape the painful truth that 'propagandists cannot win battles when the soldiers are obviously losing the war'.